An Analysis of Major Provisions of Nepalese Law of Contract (Part-V of Muluki Civil Code, 2074) - Kalika, Satya Narayan (Management Dynamics, 2020)
This doctrinal study has adopted exploratory, descriptive and analytical methods. The analysis is based on primary sources of law drawn from statutes and judicial decisions, and some secondary data drawn from articles, books and treatises on the given issue. The nascent Muluki Civil Code, 2074 contains various provisions which are important from the jurisprudential point of view of the law of contract. This paper thrives to explore the major provisions of the current law of contract in Nepal, analyse the major provisions and jurisprudence of the law of contract, while also highlighting the differences between the new and old laws regulating contract in Nepal.